2012
DOI: 10.1007/s10344-012-0666-7
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning from lead gunshot: still a threat to wild waterbirds in Britain

Abstract: Lead is a highly toxic metal known to be an important cause of morbidity and mortality in waterbirds and terrestrial birds worldwide. The risk to birds of poisoning from lead has resulted in the introduction of legislation in many countries, such as UK restrictions on the use of lead in angling weights and lead gunshot. In this study, we examined data on current and historical trends in lead poisoning in British waterbirds and related these to the introduction of legislation restricting the use of lead. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
(55 reference statements)
0
21
0
2
Order By: Relevance
“…Similarly, Newth et al . () found that 23% of Bewick's Swans found dead while wintering in Britain between 1971 and 2012 had died of lead poisoning. A recent study by Green and Pain () found a correlation between duck population trends and relative ingestion of lead, suggesting that lead poisoning can have population‐level impacts on waterbirds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Newth et al . () found that 23% of Bewick's Swans found dead while wintering in Britain between 1971 and 2012 had died of lead poisoning. A recent study by Green and Pain () found a correlation between duck population trends and relative ingestion of lead, suggesting that lead poisoning can have population‐level impacts on waterbirds.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of embedded ammunition within 31% of Bewick's Swans x-rayed on the winter grounds in Britain between the winters of 1970/71 and 2008/ 09, despite full legal protection across the flyway, suggests that illegal shooting is likely to have an impact on Bewick's Swan survival (Newth et al 2011). Similarly, Newth et al (2013) found that 23% of Bewick's Swans found dead while wintering in Britain between 1971 and 2012 had died of lead poisoning. A recent study by Green and Pain (2016) found a correlation between duck population trends and relative ingestion of lead, suggesting that lead poisoning can have population-level impacts on waterbirds.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all birds of prey scavenge, including eagles, owls, hawks, falcons, and vultures; therefore, there is potential for these and other species to be poisoned by lead (T. Katzner, personal observation; Jackowski et al ). Likewise, upland game birds and waterfowl ingest spent shotgun shot as grit (e.g., Keel et al , Walter and Reese , Newth et al , Haig et al ). Many species of waterbirds can be exposed to lead via intentionally or unintentionally discarded fishing tackle (e.g., Locke et al ).…”
Section: Lead Ingestion By Raptorsmentioning
confidence: 99%
“…Following implementation of lead tackle restrictions in the United Kingdom, there was a rapid decline in lead mortality among the mute swan ( Cygnus olor ) population (Sears and Hunt , Kirby et al , Newth et al ). Our data indicate that restrictions on the use of non‐toxic lead tackle would have similar immediate benefits to loons.…”
Section: Discussionmentioning
confidence: 99%